ORGANIC LIVESTOCK PRODUCTION – SERBIAN UNUSED CHANCE - Katić, Branko; Savić, Mirjana; Popović, Vesna (Economics of Agriculture, 2010)
The affirmation of organic production represents a man’s return to nature and more significant appreciation of its legality. The demand for the products of organic production is increasing. Serbia has extraordinary terms for significantly higher organic production, as plant, as well as livestock. It also has modern legislation which regulates this kind of production. Besides, it supports foundation of this form of production, by stimulating assets from the government budget. However, this form of production is only in the beginning. In the paper was pointed out to: courses of organic livestock production in the world and in Europe (EU), condition of this production, institutional and natural terms in Serbia for the same production, as well as on basic references for its improvement.